(3TQM GdeaUd aj UfYI GdEYQGH, GdehShe, HGdJNejQ (B/s - (3GdNhGQRej, GdbGSe Hf GdMSjf Hf CMeO,s 555-617 (3g`(B.s; (3GdYKjejf, YHO GdQMef Hf SdjeGf Hf eMeOs; (3GdReNTQj, eMehO Hf YeQ Hf eMeO,s 467-538 (3gLQjG(B.s ((3GdQjGV (B:s (3ecJHI GdYHjcGf,s, 2000)
(3TQM GdeaUd(B.s
Keywords: (3GddZI GdYQHjIs -- (3fMhs